ISO_IEC 9899_1999, Programming languages -- C - ISO/IEC (American National Standards Institute, 2011)
This International Standard specifies the form and establishes the interpretation of programs written in the C programming language.1) It specifiesthe representation of C programs; the syntax and constraints of the C language; the semantic rules for interpreting C programs; the representation of input data to be processed by C programs; the representation of output data produced by C programs; the restrictions and limits imposed by a conforming implementation of C. This International Standard does not specifythe mechanism by which C programs are transformed for use by a data-processing system; the mechanism by which C programs are invoked for use by a data-processing system; the mechanism by which input data are transformed for use by a C program; the mechanism by which output data are transformed after being produced by a C program; the size or complexity of a program and its data that will exceed the capacity of any specific data-processing system or the capacity of a particular processor; all minimal requirements of a data-processing system that is capable of supporting a conforming implementation. 1) This International Standard is designed to promote the portability of C programs among a variety of data-processing systems. It is intended for use by implementors and programmers.